The use of ai in process of interactive multimedia e-learning course development - Biziuk, A.; Ippolitova, V. (Universidad de Guanajuato Primera Edición, 2025)
In today’s information-driven world, where technology offers numerous new opportunities for learning, electronic multimedia e-learning courses are in high demand among students. These publications integrate textual information, audio, video, animation, and interactive elements, making the learning process more engaging and accessible. Moreover, they enhance the comprehension of complex concepts through visualization and interactive engagement. Modern technologies enable the adaptation of multimedia publications to the individual needs of users, ensuring a personalized learning experience.
Keywords: electronic multimedia e-learning courses; multimedia